In a State of Emergency: Martin Carter’s Poems of Resistance and Surveillance - Page, Kezia (Surveillance & Society, 2026)
This essay reads Guyanese poet, Martin Carter’s Poems of Resistance from British Guiana (2006 [1954]) as well as letters from a declassified M15 file collected in the state of emergency declared when the British invaded the colony in 1953. Using surveillance theories, particularly by Nadera Shalhoub-Kevorkian (2015), the paper discusses how surveillance works as a colonizing strategy through fear and insecurity. It argues that the heightened surveillance enacted under the emergency presents an obscene familiarity that Carter captures in close sensory imagery evoking the distortive transformation of familiar physical spaces, quotidian routines, and geographies of the mind. The close analysis of the poems focuses on Carter’s use of sound and time to come to terms with this intimate assault.